Influence of rootstock scion combinations on morpho-physiological traits in Coffee - Souza, G.F.D’; Rajeswari, N.; Ramesh Babu, H.N. (Journal of Plantation Crops, 2011)
An experiment was conducted using coffee seedlings to find out the influence of rootstock scion interactions on morpho-physiological traits. Commercially important arabica cultivars such as S.795, Sln.10 and S.4202 were grafted on drought tolerant rootstocks of arabica cultivars such as Sln.9, Sln.5 (B), Sln.11and two high vigour robusta cultivars like S.274 and C x R. Results on morpho-physiological traits indicated significant differences between rootstock scion combinations. The interaction effects in comparison with pure line seedlings of scion materials indicated that, the robusta rootstocks being diploid species (2n=22), significantly reduced the growth of tetraploid (2n=44) arabica scion materials. Results on physiological and morphological traits indicated that the higher vigour in arabica/arabica combinations compared to robusta/arabica and self graft combinations might be due to the influence of genetically divergent rootstocks of same species. Correlation analysis indicated significant positive relationship between specific leaf area and absolute growth rate (r=0.560), net assimilation rate (r=0.498) and relative leaf growth rate (r=0.587) and also leaf area duration with absolute growth rate (r=0.753) indicating role of specific leaf area and leaf area duration in governing growth and development of coffee graft combinations. The Sln.9 and Sln.5B rootstocks for S.4202 scion, Sln.5B and Sln.11 for Sln.10 scion and Sln.9 and Sln.5B rootstocks for S.795 scion were found to be efficient and could be field evaluated for yielding performance.